2011
DOI: 10.1253/circj.cj-10-0339
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Characteristics of Idiopathic Ventricular Tachycardia in Children

Abstract: Background: Idiopathic ventricular tachycardia (VT) has been reported to have a good prognosis, but there still might be the potential risk of sudden death. Methods and Results:The 46 consecutive children (mean age 11.7±3.4 years) with idiopathic VT were enrolled in this study. Monomorphic VT was detected in 39 patients and polymorphic VT in 7 patients. The VT originated from the right ventricle (RV) in 22 patients, and left ventricle (LV) in 17 patients. The VT was induced by exercise in 68% of the RVVT, 41% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
(26 reference statements)
2
8
1
Order By: Relevance
“…Although pediatric case reports and smaller case series suggest some sensitivity to adenosine, that agent was largely ineffective as an acute therapy in our population of patients with fascicular tachycardia. In studies of adult patients with left posterior fascicular tachycardia, adenosine has been shown to be ineffective, with a few exceptions …”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Although pediatric case reports and smaller case series suggest some sensitivity to adenosine, that agent was largely ineffective as an acute therapy in our population of patients with fascicular tachycardia. In studies of adult patients with left posterior fascicular tachycardia, adenosine has been shown to be ineffective, with a few exceptions …”
Section: Discussionmentioning
confidence: 76%
“…Those presenting within the first year of life may resolve spontaneously, while others require antiarrhythmic therapy and/or catheter ablation procedures. Prior reports are largely case reports and small series of patients undergoing various ablation strategies with only immediate outcome of catheter ablation described . The purpose of this study was to review clinical presentation and outcomes in pediatric patients with VT arising from left heart structures.…”
Section: Introductionmentioning
confidence: 99%
“…8 Generally, IVT in childhood and in the young is highly related to exercise and this could be characteristic of these ages. The mechanism of exercise-related VT is known to be triggered activity, but Fukuhara et al showed that variant mechanisms (not only triggered activity but also automaticity and reentry) present in this arrhythmia.…”
Section: Article P 672mentioning
confidence: 99%
“…The mechanism of exercise-related VT is known to be triggered activity, but Fukuhara et al showed that variant mechanisms (not only triggered activity but also automaticity and reentry) present in this arrhythmia. 8 Owing to technological advances in mapping and catheter ablation, the mechanisms and anatomical locations of IVT have been recognized in detail. 9 VT arising from the right and left ventricular outlet tracts (RVOT, LVOT) has similar characteristics because of a common embryonic origin.…”
Section: Article P 672mentioning
confidence: 99%
“…3,4 The poor response to medical therapy, haemodynamic instability seen during tachycardia in some cases, and good response to ablation therapy have increased the importance of this technique. 5,6 However, left posterior fascicular ventricular tachycardia catheter ablation remains challenging in the pediatric population, and most studies about this topic have been conducted on adult patients. Moreover, there is not any study in the literature that focuses on reducing the use of fluoroscopy by using three-dimensional electroanatomical mapping systems in pediatric left posterior fascicular ventricular tachycardia ablations.…”
Section: Introductionmentioning
confidence: 99%